Pengaruh Service Quality terhadap Customer Satisfaction Dimediasi oleh Customer Experience pada Bengkel Intan Motor Baleendah - M. Bagas Andi Rifki; Akbar Rohandi, Moch. Malik (Bandung Conference Series: Business and Management, 2024)
Abstract. The condition of automotive business competition is getting tighter every day, a company must be able to fulfill one thing, namely satisfying consumers so that consumers can survive and the company can dominate the market, in line with this, the company must be able to improve service quality as well as possible. This study focuses on the variables of Service Quality, Customer Experience, and Customer Satisfaction. The purpose of this study is to determine the relationship between service quality and customer satisfaction and the role of customer experience as a mediating / intervening variable for consumers at the Intan Motor Baleendah Workshop. The research method used in this research is a survey method with a tool in the form of a questionnaire as a data collection technique. The object of this research is consumers at the Intan Motor Baleendah Workshop, who are mainly domiciled in Bandung Regency, totaling 120 respondents. The sampling technique used in this study was purposive sampling. There are four hypotheses formulated in this study. The techniques used to test the hypothesis are simple linear regression, sobel test and path analysis. The results showed that service quality has a positive and significant effect on customer experience, customer experience has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction¸ customer experience is able to mediate the effect of service quality on customer satisfaction at the Intan Motor Baleendah Workshop. Abstrak. Kondisi persaingan usaha otomotif yang semakin hari semakin ketat, suatu perusahaan harus bisa memenuhi suatu hal yakni memuaskan konsumen sehingga konsumen dapat bertahan dan perusahaan tersebut dapat menguasai pasar, sejalan dengan hal tersebut maka perusahaan harus bisa meningkatkan kualitas pelayanan dengan sebaik mungkin. Penelitian ini berfokus pada variabel Service Quality, Customer Experience, dan Customer Satisfaction. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara service quality dan customer satisfaction serta peran customer experience sebagai variabel mediasi/intervening pada konsumen di Bengkel Intan Motor Baleendah. Metode penelitian yang digunakan pada penelitian ini adalah metode survei dengan alat berupa kuesioner sebagai teknik pengumpulan data. Objek penelitian ini adalah konsumen di Bengkel Intan Motor Baleendah yang khususnya berdomisili di Kabupaten Bandung. Teknik sampling yang digunakan pada penelitian ini adalah purposive sampling. Terdapat empat hipotesis yang dirumuskan pada penelitian ini. Teknik yang digunakan untuk menguji hipotesis adalah regresi linier sederhana, uji sobel dan path analysis (analisis jalur). Hasil penelitian menunjukkan bahwa¸ customer experience mampu memediasi pengaruh service quality terhadap customer satisfaction pada Bengkel Intan Motor Baleendah.